2020
DOI: 10.21203/rs.3.rs-18571/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making a case for preconception care—the pregnancy experiences of women with pre-existing medical conditions in Ibadan, Nigeria

Abstract: BackgroundFactors that predispose to poor maternal and child health outcomes in most low and middle income countries include the presence of pre-existing medical conditions that are amenable to preconception care (PCC). Nigeria has an increasing pool of women of reproductive age with pre-existing medical conditions but PCC services are not provided routinely in the maternal and child health framework. This study explores the pregnancy experiences of women with pre-existing medical conditions to make a case for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
2
2
0
Order By: Relevance
“…The results also revealed that general assessment, genetic counselling or referral for genetic service, risk assessment, referral to the doctor for adjustment of treatment and giving of supplements was not performed. These findings are similar to the findings of Ojifinni and Ibisomi [ 19 ], where it was found that most clients, even those with chronic conditions such as hypertension, were not offered PCC even though it was indicated. Women who were advised about the importance of postponing pregnancy until their viral load was low or undetectable were not given any supplements.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results also revealed that general assessment, genetic counselling or referral for genetic service, risk assessment, referral to the doctor for adjustment of treatment and giving of supplements was not performed. These findings are similar to the findings of Ojifinni and Ibisomi [ 19 ], where it was found that most clients, even those with chronic conditions such as hypertension, were not offered PCC even though it was indicated. Women who were advised about the importance of postponing pregnancy until their viral load was low or undetectable were not given any supplements.…”
Section: Discussionsupporting
confidence: 90%
“…The participants in this study indicated that women with chronic conditions were referred to high-risk clinics when they are pregnant. Ojifinni and Ibisomi [19] supported the above findings.…”
Section: Discussionsupporting
confidence: 58%
“…this might be explained as those having pre-existing medical conditions entirely worry about their medical condition than using preconception care service. Also, a study conducted in Nigeria showed that none of the participants with pre-existing medical conditions had awareness of PCC [63].…”
Section: Plos Onementioning
confidence: 99%
“…Although there is some evidence that men who are preparing to be fathers may be concerned about their health, they may not be receiving adequate information about risk factors and critical issues because health care providers are not aware or trained to provide the service ( 10 , 46 ). A study among Nigerian women with pre-existing medical conditions showed missed opportunities for PCC services despite regular contact with the health system on account of their past medical history ( 47 ). These factors, coupled with a lack of awareness among health care workers as described in this study may explain the reluctance with which men approach reproductive health services.…”
Section: Discussionmentioning
confidence: 99%